(untitled) (Khairulummah, 2023)
Parents who spend time with their children at home and assist them in study bring positive results in their kid’s academic performance. Therefore, for effective learning there is a need of active contact between the school instructional practices and leaners families. This study hypothesize that there is a positive correlation between active participation of parents and children educational achievement. in In the study Parental Involvement has been chosen as an independent variable and Academic Performance as the dependent variable. Indicators of Parental Involvement are, assistance to student, discussion, support in homework and contact with instructor. Academic Performance represented in higher grades, test scores, and better school attendance Methodology employed is qualitative, data collection mainly draw from parents of the 137 students (girls) through personal interview and questionnaire, registered at school, the Frontier Science Academy Hayatabad, Peshawar, of Khyber Pukhtun khwa. Data was analyzed through SPSS percentage frequency distribution and produced findings and conclusions. Grade 8 female students were taken as respondents.